2016
DOI: 10.1007/s10934-016-0316-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nanopores arrangement of anodic alumina layers synthesized on low-(AA1050) and high-purity aluminum by two-step anodizing in sulfuric acid with addition of ethylene glycol at low temperature

Abstract: In this work the anodic aluminum oxide (AAO) was produced by two-step self-organized anodization of two classes purity aluminum in 0.3 M sulfuric acid aqueous solution with addition of ethylene glycol as the solution modifier. The arrangement analysis method based on fast Fourier transforms was applied to characterize the porous arrays ordering. The quality, arrangement, circularity and regularity of nanoporous AAO formed on the low-purity (AA1050) and high-purity aluminum were investigated in details. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
1
12
1
3
Order By: Relevance
“…Additionally, the anodization in a broader range of potential is possible without burning phenomenon. Yet, above certain critical potential values, hillocks and cracks occur decreasing the quality of resulting NAA [ 99 ]. The presence of ethylene glycol in the electrolyte for aluminum anodization facilitates oxidation of the intermetallic phase.…”
Section: Nanoporous Anodic Alumina (Naa): Definition and Formationmentioning
confidence: 99%
“…Additionally, the anodization in a broader range of potential is possible without burning phenomenon. Yet, above certain critical potential values, hillocks and cracks occur decreasing the quality of resulting NAA [ 99 ]. The presence of ethylene glycol in the electrolyte for aluminum anodization facilitates oxidation of the intermetallic phase.…”
Section: Nanoporous Anodic Alumina (Naa): Definition and Formationmentioning
confidence: 99%
“…In our study, we found that the fluoride anions preferably incorporate from glycerine-based electrolyte in the anodic matrix. As was published before, in the case of aluminum anodization, the differences in electrolyte viscosity influence the amount of incorporated electrolyte species into the anodic oxide [ 22 , 23 , 24 ]. In this research, similar to the case of aluminum anodization, the difference in the viscosity of the electrolyte strongly affected the chemical composition of anodic titanium oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Anodization conditions are important factors allowing the control of anodic oxides morphology where, among others, the electrolyte viscosity has a significant influence on the anodization process and the resulting oxides [ 20 , 22 , 23 , 24 ]. The electrolyte viscosity is inversely proportional to the ionic mobility and the electrical conductivity of the electrolyte [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the deposition of metals inside the pores of the Al 2 О 3 -matrices is successfully applied for the formation of functional coatings, having a number of practical applications. The AAO layers, modified with Cu [12][13][14][15][16][17][18][19][20], Ni [21][22][23][24][25][26][27][28][29] and combined Cu and Ni [30][31][32][33][34], are implemented as decorative and corrosion protective coatings [35][36][37][38][39][40][41][42][43][44][45], as well as solar absorbers [22,24,25].…”
Section: Introductionmentioning
confidence: 99%